Operational efficiency in banking: An international comparison Reply to the comment - Allen, Linda; Rai, Anoop (Journal of Banking & Finance, 1997)
To avoid problems associated with Jensen's inequality, we use a corrected inefficiency measure to compare the estimate of inefficiency obtained using the distribution free (DF) method with the estimate obtained using the stochastic cost frontier (SCF). The results of the paper are unchanged. The DF method yields measures of inefficiency that are significantly higher than measures obtained using the SCF.